Alpha1-antitrypsin phenotypes in sex chromosome mosaicism. Issue 3 (September 1975) - Kueppers, F; O'Brien, P; Passarge, E; Rüdiger, H W
Abstract : We report the alpha1-antitrypsin phenotypes of 21 patients with sex chromosome mosaicism and their parents. The proportion of heterozygotes in the group of parents is significantly greater (p less than 0.01) than that proportion in both control groups. The maternal or paternal contribution to the statistical significance of this observation cannot be distinguished in our small sample of families.